Development of a drosophila CMT model via overexpression and knocking-in of GDAP1 gene - Akyüz, Hüseyin Kaya. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Charcot-Marie-Tooth (CMT) disease is one of the most common inherited disorders of the nervous system. Known also as hereditary motor and sensory neuropathy, this disease is characterized by distal sensory loss, muscle weakness and atrophy, loss of deep tendon reflexes and skeletal deformities, especially in the lower extremities. However, genetically, it is a highly heterogeneous disease, with mutations in approximately 40 genes associated with the disease. GDAP1 is one of the most frequently mutated genes among recessively inherited CMT though it also exhibits dominant segregation. As its mutations may cause demyelinating, axonal and intermediate subtypes of the disease and mostly severe and early onset neuropathy, it is an important candidate to study. In the scope of this research, we have aimed to develop a Drosophila CMT model using overexpression of its ortholog in flies and generation of various knock-in constructs. The second aim of this study is to understand the functions of GDAP1, which is a mitochondrial fission factor with glutathione S-transferase activity, and CG4623 that is an uncharacterized protein. In the first part of the study, tools have been generated for integrase-mediated approach for gene knock-out. Among these are constructs for knocking-in human GDAP1 and CMT-causing nine mutant forms of GDAP1 in place of its Drosophila homolog (CG4623), a GAL4 driver and an mCherry reporter for CG4623. Along with these, the initial steps of anti-CG4623 antibody production have been taken. In the second part of the project, a fly line overexpressing CG4623 under UAS control has been generated in order to understand the function of this gene and to compare it to its ortholog in humans. Lastly, available mutant lines for mitochondrial dynamics-related genes have been used in analyses of longevity and mitochondrial dynamics, which may be adapted for analyses of the knock-in and overexpression lines. With this study, our final goal is to shed light on the pathogenesis of CMT through understanding the function of GDAP1 and its role in neuropathy by starting the fly model for the disease in our laboratory.
Keywords: Charcot-Marie-Tooth disease.; Genetic disorders.